General care for patients with chronic obstructive pulmonary disease in intensive care - Dos Santos, Jéssica Batista; Ana Claudia Rodrigues; Muniz, Monyck Maria Da Silva; Bitar, Anna Camilly Oliveira; Cavalcante, Deives Aurélio Melo Da Rocha; Rocha, Claudia Aparecida Godoy (Seven Editora, 2023)
This study focuses on the discussion about the nursing care provided to patients with Chronic Obstructive Pulmonary Disease (COPD) in intensive care. COPD is understood as a change in the sending of oxygen in the airways toward the lungs. This alteration compromises the functions of the lungs causing diseases such as chronic bronchitis, and obstructive bronchiolitis, due to its inflammation, to further damage the pulmonary structures, as well as the production of substances harmful to the individual's health (1, 2).  DOI: https://doi.org/10.56238/colleinternhealthscienv1-129